PHYTOCHEMICAL SCREENING AND DPPH FREE RADICAL SCAVENGING ACTIVITY OF AFRICAN TULIP (Spathodea campanulata) LEAVES - I. C, AZUAGA; T. I, AZUAGA; U.G, IBRAHIM; O. A, USHIE; K.V, DOUGLAS (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Spathodea campanulata is commonly used in Nigeria traditional medicines to cure different ailments. Parts of Spathodea campanulata such as leaves, have been reported for possessing anti-inflammatory, analgesic, cytotoxic, anti-diabetic and anticonvulsant activity. In this study, preliminary phytochemical screening of the leaves was carried out and the results revealed the presence of different secondary metabolites like alkaloids, flavonoids, saponins and tannins. The antioxidant activity of the crude extract of Spathodea campanulata was also studied. The crude extracts (n-hexane, ethyl acetate and methanol) were obtained using cold maceration method by soaking 100 g of the sample in 250 mL hexane for 72 hours with frequent agitation. The procedure was repeated on the residue using ethyl acetate and methanol. The extracts were analyzed for their antioxidant activity using 2, 2- diphenyl-1picryl-hydrazyl (DPPH) radical to evaluate their free radical scavenging activity. Ascorbic acid was used as the standard antioxidant. The results showed that the extracts inhibited DPPH radical in a concentration of 0.03, 0.62, 0.12, 0.25, and 0.5 mg/L with percentage inhibition in the range of 46.78% to 86.26% for all the extract which was not significantly different as compared with ascorbic acid (82.61% to 85.74%). From the findings of this study, Spathodea campanulata leaf extracts have the ability to inhibit free radical species induced damage. Also, the findings further support the reported claims of its antiinflammatory, analgesic anti-diabetic and anticonvulsant activity